2019
DOI: 10.1038/s41598-019-42061-9
|View full text |Cite
|
Sign up to set email alerts
|

The serum level of irisin, but not asprosin, is abnormal in polycystic ovary syndrome patients

Abstract: Polycystic ovary syndrome (PCOS) is a disorder characterized by hyperandrogenism, oligo- or anovulation, and/or polycystic ovary. It frequently presents with dyslipidemia and insulin resistance. Recent studies have shown that the white adipose tissue-derived asprosin is elevated in humans with insulin resistance. Because many PCOS patients have a propensity to develop dyslipidemia and/or insulin resistance, asprosin metabolism could be dysregulated in PCOS patients. Accordingly, we investigated serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 65 publications
(44 reference statements)
6
37
2
Order By: Relevance
“…Previous studies have shown that circulating ZAG, Irisin and Betatrophin concentrations were significantly reduced or elevated in patients with T2DM or PCOS, respectively, and were associated with IR [10][11][12][20][21][22]. In addition, a recent meta-analysis and other populations had indicated that serum irisin concentration in PCOS women were higher than that in healthy women, this elevaluation could be partly attributed to the BMI in PCOS patients [23][24][25][26]. Therefore, most studies have revealed that circulating Irisin levels indeed has a tendency to increase in PCOS women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that circulating ZAG, Irisin and Betatrophin concentrations were significantly reduced or elevated in patients with T2DM or PCOS, respectively, and were associated with IR [10][11][12][20][21][22]. In addition, a recent meta-analysis and other populations had indicated that serum irisin concentration in PCOS women were higher than that in healthy women, this elevaluation could be partly attributed to the BMI in PCOS patients [23][24][25][26]. Therefore, most studies have revealed that circulating Irisin levels indeed has a tendency to increase in PCOS women.…”
Section: Discussionmentioning
confidence: 97%
“…In PCOS patients, circulating ZAG levels were reported to be consistently reduced [10,27,28]. However, the relationship between circulating betatrophin levels and PCOS is controversial and the studies in the literature are inconsistent [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Growing evidence indicates that these cytokines have some roles in the pathogenesis of T2DM and PCOS, and are also involved in IR development.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research reported that the metabolic characteristics of PCOS patients differed significantly from those of diabetes mellitus patients. The finding suggested that the levels of irisin were abnormal in PCOS patients, while the exact links between plasma asprosin levels and the metabolic manifestation in patients with PCOS could not be observed (30). Together, whether there is a correlation between asprosin and POCS and whether asprosin can be used as a biomarker for predicting and diagnosing PCOS remain to be further studied.…”
Section: Asprosin In Pcosmentioning
confidence: 98%
“…Recently, two other groups confirmed that asprosin was positively correlated with diabetes mellitus [16,23]. There have been reports about the relationship between asprosin and PCOS; however, these results are inconsistent [13,15,24]. We would like to further explore the profiles of asprosin in PCOS subtypes, and HA is one of the most important phenotypes of PCOS.…”
Section: / 16mentioning
confidence: 91%
“…Our study provides significant insights about the correlation between asprosin and PCOS. Three different studies about asprosin and PCOS were recently published [13,15,24]. Chia et al reported that asprosin levels in women with PCOS were similar to those in corresponding controls [24].…”
Section: / 16mentioning
confidence: 99%